Evaluating Differences in Opioid and Stimulant Use-associated Infectious Disease Hospitalizations in Florida, 2016–2017. (4th September 2020) - Serota, David P; Bartholomew, Tyler S; Tookes, Hansel E
Abstract: Background: The opioid epidemic has led to increases in injection drug use (IDU)-associated infectious diseases; however, little is known about how more recent increases in stimulant use have affected the incidence and outcomes of hospitalizations for infections among people who inject drugs (PWID). Methods: All hospitalizations of PWID for IDU-associated infections in Florida were identified using administrative diagnostic codes and were grouped by substance used (opioids, stimulants, or both) and site of infection. We evaluated the association between substance used and the outcomes: patient-directed discharge (PDD, or "against medical advice") and in-hospital mortality. Results: There were 22 856 hospitalizations for infections among PWID. Opioid use was present in 73%, any stimulants in 43%, and stimulants-only in 27%. Skin and soft tissue infection was present in 50%, sepsis/bacteremia in 52%, osteomyelitis in 10%, and endocarditis in 10%. PWID using opioids/stimulants were youngest, most uninsured, and had the highest rates of endocarditis (16%) and hepatitis C (44%). Additionally, 25% of patients with opioid/stimulant use had PDD versus 12% for those using opioids-only. In adjusted models, opioid/stimulant use was associated with PDD compared to opioid-only use (aRR 1.28, 95% CI 1.17–1.40). Younger age and endocarditis were also associated with PDD. Compared to opioid-only use, stimulant-only use had higher risk of in-hospital mortality (aRR 1.26, 95% CI 1.03–1.46). Conclusions: While opioid use contributed to most IDU-associated infections, many hospitalizations also involved stimulants. Increasing access to harm reduction interventions could help prevent these infections, while further research on the acute management of stimulant use disorder-associated infections is needed. Abstract : Among people hospitalized with injection drug use-associated infections in Florida, those with both stimulant and opioid use were more likely to have endocarditis and to have patient-directed discharge compared to those using opioids-only. Stimulant-only use was associated with in-hospital mortality.